2021
DOI: 10.1111/ajt.16547
|View full text |Cite
|
Sign up to set email alerts
|

Distinct immunopathological mechanisms of EBV-positive and EBV-negative posttransplant lymphoproliferative disorders

Abstract: EBV‐positive and EBV‐negative posttransplant lymphoproliferative disorders (PTLDs) arise in different immunovirological contexts and might have distinct pathophysiologies. To examine this hypothesis, we conducted a multicentric prospective study with 56 EBV‐positive and 39 EBV‐negative PTLD patients of the K‐VIROGREF cohort, recruited at PTLD diagnosis and before treatment (2013–2019), and compared them to PTLD‐free Transplant Controls (TC, n = 21). We measured absolute lymphocyte counts (n = 108), analyzed NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…While most adult transplant recipients have encountered EBV before transplantation, pediatric transplant recipients are less likely to and therefore more frequently develop primary EBV primary infection after transplantation. A recent study by our team observed that the NK cells of adult PTLD patients overexpress the HLA-DR activation marker, with the highest levels observed in patients who acquired primary EBV infection post-transplant [32]. In that same study, NK cell activation was associated with high EBV loads and seemed to cause NK cell apoptosis, as those patients also presented with high proportions of IFN-γ-producing NK cells, PD-1 overexpression and profound NK cell lymphopenia [32] (Figure 1).…”
Section: Nk Cells and Ebv-positive Ptldsmentioning
confidence: 90%
See 4 more Smart Citations
“…While most adult transplant recipients have encountered EBV before transplantation, pediatric transplant recipients are less likely to and therefore more frequently develop primary EBV primary infection after transplantation. A recent study by our team observed that the NK cells of adult PTLD patients overexpress the HLA-DR activation marker, with the highest levels observed in patients who acquired primary EBV infection post-transplant [32]. In that same study, NK cell activation was associated with high EBV loads and seemed to cause NK cell apoptosis, as those patients also presented with high proportions of IFN-γ-producing NK cells, PD-1 overexpression and profound NK cell lymphopenia [32] (Figure 1).…”
Section: Nk Cells and Ebv-positive Ptldsmentioning
confidence: 90%
“…A recent study by our team observed that the NK cells of adult PTLD patients overexpress the HLA-DR activation marker, with the highest levels observed in patients who acquired primary EBV infection post-transplant [32]. In that same study, NK cell activation was associated with high EBV loads and seemed to cause NK cell apoptosis, as those patients also presented with high proportions of IFN-γ-producing NK cells, PD-1 overexpression and profound NK cell lymphopenia [32] (Figure 1). Altogether, the different alterations of NK cells that have been described at EBV-positive PTLD diagnosis seem to be directly related to the interaction between EBV and NK cells in the context of immunosuppression and reduced presence of adaptive T lymphocytes.…”
Section: Nk Cells and Ebv-positive Ptldsmentioning
confidence: 90%
See 3 more Smart Citations